Thyroid hormones profiling in pregnant women at various gestational periods - Bray, Rosemond Lorreta (2012)
This Thesis has been submitted in partial fulfilment of the requirement for the M. Sc degree in Clinical Biochemistry at the Department of Molecular Medicine, School of Medical Sciences,Kwame Nkrumah University Of Science and Technology, Kumasi, Ghana.